Enhanced degradation of anthraquinone dyes by microbial monoculture and developed consortium through the production of specific enzymes - Mohanty, Swati Sambita; Kumar, Arvind (Scientific reports, 2021)
The current study investigates the decolorization of Indanthrene Blue RS dye and the optimization of process parameters needed for effective decolorization by the bacterial consortium. The pure culture of strain TS8, PMS, and NCH has been isolated from the textile wastewater sample collected from local textile processing units outlet and dye contaminated soil from Odisha, India. A bacterial consortium-BP of Bacillus flexus TS8 (BF), Proteus mirabilis PMS (PM), and Pseudomonas aeruginosa NCH (PA) were developed. The physicochemical parameters were optimized to attain maximum decolorization efficacy. Degradation of Indanthrene Blue RS and the formation of metabolites were confirmed through UV–vis spectroscopy, FT-IR, and GC–MS analysis. The developed consortium-BP showed an enhanced decolorization of Indanthrene Blue RS dye with an Average decolorization rate of 11,088 µg h −1 within 9 h compared to the individual strains under aerobic conditions. The supplementation of agricultural residual wastes showed increased decolorization efficiency of consortium-BP. Higher reduction in TOC and COD removal (≥ 80%) determined the mineralization of Indanthrene Blue RS by consortium-BP. Significant induction of various oxidoreductive enzymes in consortium-BP compared to that of Individual strains indicates their involvement in the overall decolorization and degradation process, with the higher protein concentration in the intracellular enzymes. Studies on the phytotoxicity effect revealed the non-toxic nature of the degraded products formed on mineralization of Indanthrene Blue RS by consortium-BP. This study represents a new approach for enhanced biodegradation using consortium-BP in treating textile wastewaters containing anthraquinone dyes.